Effects of preoperative and postoperative resistance exercise interventions on recovery of physical function in patients undergoing abdominal surgery for cancer: a systematic review of randomised controlled trials. Issue 1 (25th April 2018) - Stephensen, David; Hashem, Ferhana; Corbett, Kevin; Bates, Amanda; George, Michelle; Hobbs, Ralph Peter; Hopkins, Malcolm; Hutchins, Irena; Lowery, David Peter; Pellatt-Higgins, Tracy; Stavropoulou, Charitini; Swaine, Ian; et al.
Abstract : Objective: To systematically review the effects of preoperative and postoperative resistance exercise training on the recovery of physical function in patients undergoing abdominal surgery for cancer. Data sources: A systematic review of English articles using Medline, Physiotherapy Evidence Database, CINAHL and the Cochrane Library electronic databases was undertaken. Eligibility criteria for selecting studies: Studies were included if they used a randomised, quasi-randomised or controlled trial study design and compared the effects of a muscle-strengthening exercise intervention (±other therapy) with a comparative non-exercise group; involved adult participants (≥18 years) who had elected to undergo abdominal surgery for cancer; and used muscle strength, physical function, self-reported functional ability, range of motion and/or a performance-based test as an outcome measure. Results: Following screening of titles and abstracts of the 588 publications retrieved from the initial search, 24 studies met the inclusion criteria and were accessed for review of the full-text version of the article, and 2 eligible studies met the inclusion criteria and were included in the review. One exercise programme was undertaken preoperatively and the other postoperatively, until discharge from hospital. The exercise interventions of the included studies were performed for five and eight sessions, respectively. There were no differences between groups in either study. Conclusion: The only two studies designed to determine whether preoperative or postoperative resistance muscle-strengthening exercise programmes improved or negatively affected physical function outcomes in patients undergoing abdominal surgery for cancer provide inconclusive results.